2014
DOI: 10.1093/geronb/gbu011
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Paradox of Well-being: The Importance of National Context

Abstract: The findings clarify the relationship between age and SWB by demonstrating that the paradox of well-being is conditional on the economic context. Implications for individual- and country-level strategies for successful aging are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 45 publications
5
57
0
6
Order By: Relevance
“…Although this premise was supported in this sample, other groups of adults do not display this age-related pattern. For example, one study found that older age was related to lower levels of well-being (defined as self-reported levels of happiness and satisfaction) in countries where the gross domestic product (GDP) was low (Swift et al, 2014). This finding, therefore, suggests that a worse economic climate creates a context where “the paradox of aging” is not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Although this premise was supported in this sample, other groups of adults do not display this age-related pattern. For example, one study found that older age was related to lower levels of well-being (defined as self-reported levels of happiness and satisfaction) in countries where the gross domestic product (GDP) was low (Swift et al, 2014). This finding, therefore, suggests that a worse economic climate creates a context where “the paradox of aging” is not observed.…”
Section: Discussionmentioning
confidence: 99%
“…SOC may be related to quality of later life as structured by the allocation of public resources to older adults-a metric on which Sweden performs quite favorably. Supporting this interpretation is research by Swift et al (2014) that examined variation in happiness and life satisfaction by age across 27 countries. This research found that subjective well-being improved after age 60 only after income, marital status, and health were controlled and primarily in wealthier countries.…”
Section: Predictorsmentioning
confidence: 99%
“…Different age cohorts tend to utilize different experiences and resources to respond to the same historical event or condition, resulting in cohort-patterned LS trajectories. For instance, a study found that economic context affects older people more than younger people (Swift et al, 2014). …”
Section: Introductionmentioning
confidence: 99%